2006
DOI: 10.1111/j.1524-4725.2005.31103
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles in Varicose Veins Using Complementary DNA Microarray

Abstract: Many up-regulated genes were found in Ws by applying cDNA microarray. These gene profiles suggested a pathway associated with fibrosis and that wound healing might be related to the pathophysiology of VVs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…Complementary DNA (cDNA) microarrays comparing the differential gene expression of varicose and nonvaricose veins show an upregulation of 82 genes of the 3063 cDNA clones in varices. The upregulated genes include those of ECM molecules, cytoskeletal proteins and myofibroblasts such as transforming growth factor β-induced gene (BIGH3), tubulin, lumican, actinin, type I collagen, versican, actin and tropomyosin 49 . It has also been shown that three cDNAs similar to the L1M4 repeat sequence of clone RP11-57L9, clone RP11-299H13, and Alu repetitive sequence of human tropomycin 4 mRNA are expressed differently in varicose compared with nonvaricose veins 50 .…”
Section: Genes Regulating Vein Wall Structurementioning
confidence: 99%
“…Complementary DNA (cDNA) microarrays comparing the differential gene expression of varicose and nonvaricose veins show an upregulation of 82 genes of the 3063 cDNA clones in varices. The upregulated genes include those of ECM molecules, cytoskeletal proteins and myofibroblasts such as transforming growth factor β-induced gene (BIGH3), tubulin, lumican, actinin, type I collagen, versican, actin and tropomyosin 49 . It has also been shown that three cDNAs similar to the L1M4 repeat sequence of clone RP11-57L9, clone RP11-299H13, and Alu repetitive sequence of human tropomycin 4 mRNA are expressed differently in varicose compared with nonvaricose veins 50 .…”
Section: Genes Regulating Vein Wall Structurementioning
confidence: 99%
“…Also, patients with Klippel-Trenaunay syndrome often have VVs, supporting heritability of VVs (Delis et al, 2007). Other evidence for a genetic component of VVs include the following: a heterozygous mutation in the Notch3 gene identified in the cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy pedigree with VVs (Saiki et al, 2006); a microarray analysis of 3063 human cDNAs from VVs showing upregulation of 82 genes, particularly those regulating ECM, cytoskeletal proteins, and myofibroblast production (Lee et al, 2005); individuals with Ehlers-Danlos syndrome type IV being prone to vascular pathology and VVs (Badauy et al, 2007); identification of single nucleotide polymorphisms in the promoter region of the MMP-9 gene among Chinese patients with VVs, with a 1562 C-to-T substitution associated with increased MMP-9 promoter activity and plasma levels (Xu et al, 2011); and the reduction of the elasticity of the lower-limb vein wall in children of VV patients (Reagan and Folse, 1971). …”
Section: Chronic Venous Diseasementioning
confidence: 99%
“…Family history and genetic and hereditary factors could also contribute to the risk for VVs (Lee et al, 2005). Primary lymphedema-distichiasis, a rare syndrome characterized by a mutation in the FOXC2 region of chromosome 16, is associated with VVs at an early age (Ng et al, 2005).…”
Section: Chronic Venous Diseasementioning
confidence: 99%
“…Важно отметить, что в ряде исследований [43] (информация по которым не представлена в табли-це) показали различия между варикозными и ин-тактными венами в экспрессии многих генов, в том числе структурных генов, регулирующих внеклеточ-ный матрикс, белки цитоскелета и миофибробла-сты. Однако остается неясным, является ли диффе-ренциальная экспрессия этих генов причиной или эффектом ВРВ [44].…”
unclassified